The Act of Silencing in Robert Musil’s “Tonka” - Harfiyah Widiawati; Lambok Hermanto Sihombing; Aris Masruri Harahap (Politeknik Negeri Padang, 2020)
Modernism’s overemphasize on universal objectivity as well as its optimistic humanism have generated critical questions. The critics on modernism, labeled under the name of postmodernists, question the neutrality assumed by humanist universalism and scientific objectivism. Seeing the ugly sides of enlightenments, the modernist critics begins to see modernism “as deeply implicated by forms of oppression: sexism, racism, class-ism, colonialism”. The purpose of this paper is to analyze a modernist work from the view point of postmodernism. The work that is under discussion here is “Tonka” by Robert Musil. Within the story, we can see that a form of oppression appears. We are to find how the form of oppression within the story works. It is interesting to find that the oppression works through the act of silencing. To see how silence is interwoven in the story, we have to firstly set some limitation to make possible the discussion on silence itself. The easiest way to do it is by putting the entity in a binary opposition since the text strongly shows binary organization.